Sacra Pagina: 1, 2, and 3 John - Painter, John (Book collections on Project MUSE., 2002)
The Johannine Epistles are today read as an important part of the Johannine literature. Yet the meaning of the text is often unclear. Part of the problem arises because, although 1 John is called an Epistle, it lacks the formal marks of an Epistle. In 1, 2, and 3 John, John Painter illuminates the relationship 1, 2, and 3 John have to each other and to the Gospel.